2015
DOI: 10.1007/s00204-015-1486-9
|View full text |Cite
|
Sign up to set email alerts
|

Polyhexamethylene guanidine phosphate aerosol particles induce pulmonary inflammatory and fibrotic responses

Abstract: Polyhexamethylene guanidine (PHMG) phosphate was used as a disinfectant for the prevention of microorganism growth in humidifiers, without recognizing that a change of exposure route might cause significant health effects. Epidemiological studies reported that the use of humidifier disinfectant containing PHMG-phosphate can provoke pulmonary fibrosis. However, the pulmonary toxicity of PHMG-phosphate aerosol particles is unknown yet. This study aimed to elucidate the toxicological relationship between PHMG-pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
70
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 43 publications
5
70
0
1
Order By: Relevance
“…In addition, TGF-β levels increase markedly in airway epithelial cells exposed to PHMG-P (Kim et al, 2016a), mirroring similar significant increases observed in cases associated with humidifier disinfectant exposure (Kim et al, 2016b). TGF-β is a growth factor produced in alveolar macrophages and epithelial cells, which stimulates fibroblasts to produce interstitial components such as fibronectin and collagen, and also promotes the proliferation and migration of pulmonary fibroblasts.…”
Section: Mechanism Of Phmg-p-induced Lung Toxicitysupporting
confidence: 54%
See 4 more Smart Citations
“…In addition, TGF-β levels increase markedly in airway epithelial cells exposed to PHMG-P (Kim et al, 2016a), mirroring similar significant increases observed in cases associated with humidifier disinfectant exposure (Kim et al, 2016b). TGF-β is a growth factor produced in alveolar macrophages and epithelial cells, which stimulates fibroblasts to produce interstitial components such as fibronectin and collagen, and also promotes the proliferation and migration of pulmonary fibroblasts.…”
Section: Mechanism Of Phmg-p-induced Lung Toxicitysupporting
confidence: 54%
“…Moreover, inflammatory cell foci and collagen accumulation appeared in the interstitial, peribronchiolar, and perivascular areas in a concentration-dependent manner ( Fig. 2; Kim et al, 2016a).…”
Section: Lung Toxicity Of Phmg-pmentioning
confidence: 90%
See 3 more Smart Citations